If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -6(x + -1) = 1 Reorder the terms: 9x + -6(-1 + x) = 1 9x + (-1 * -6 + x * -6) = 1 9x + (6 + -6x) = 1 Reorder the terms: 6 + 9x + -6x = 1 Combine like terms: 9x + -6x = 3x 6 + 3x = 1 Solving 6 + 3x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 1 + -6 3x = 1 + -6 Combine like terms: 1 + -6 = -5 3x = -5 Divide each side by '3'. x = -1.666666667 Simplifying x = -1.666666667
| 6(d-6)=4(d-60)+2d | | -7x+(-7x-30)=36 | | 9mn/4n | | -2x^2+6x+8=12 | | -1=-5-4s | | 18z^3+9z^2-50z-25=0 | | x^2=y^2-20.25 | | 4(-5x+35)-x+7=0 | | 5x/2-8=2x-7/6 | | 2s+7=-5s | | 10a-83=203 | | X=(18+8) | | x=(x)(x) | | 34-2x=80 | | X^2-76+1380=0 | | 258=175-w | | 250=10e | | -2(2q-4)=10q-20 | | 11y+12=45 | | Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 | | 8k-8=24 | | 1.5a=-12 | | -5.9=w+6.1 |